Fermentation of sugar kelp (Saccharina latissima): exploring the potential of the kelp’s native microbiota as starter culture and the microbiological food safety of fermented products - Stévant, Pierrick; Zioga, Evangelia; Steenholdt Sørensen, Jonas; Heiner Bang-Berthelsen, Claus; Dahl, Thomas Hagby; Barnung, Trygg; Kleppe, Malin; Løvdal, Trond (Frontiers in Food Science and Technology, 2025)
This study investigated the use of native microbiota from the sugar kelp Saccharina latissima, in the form of fermented kelp fluid (FKF) from a spontaneous anaerobic fermentation process, as a starter culture (SC) for the fermentation of freshly harvested biomass of the same species. Rapid (< 48 h) acidification (pH < 4.3) was achieved for S. latissima inoculated with FKF, at a fermentation temperature of 21 °C. Kelp inoculated with a commercial strain of Lactiplantibacillus plantarum (Lp, positive control) reached a similar pH level after 5 days, while kelp with no SC (negative control) did not reach a pH level below 4.3 within nine days. The microbiota of the FKF-SC as well as the FKFinoculated S. latissima samples was dominated by lactic acid bacteria (LAB) identified as L. plantarum.The SC in these samples successfully converted mannitol into lactic acid as the main fermentation product. In contrast, a higher production of acetic acid and ethanol was measured in the negative control samples compared to other groups reflecting a different microbial profile including marine bacteria which could not be identified by MALDI-TOF biotyping. Challenge trials of S. latissima samples from experimental and commercial fermentation processes with Bacillus cereus did not result in the growth of this food pathogen, even at pH levels within viable range for this species (pH > 4.3). These preliminary results provide a foundation for further isolation of suitable SCs for kelp fermentation in commercial production and for assessing the food safety of fermented kelp.